Chasing the unbiased willingness to pay: Using an integrated contingent valuation survey in estimating the non-market value of rubber plantation ecological restoration programs in China - Qiao, Dan; Liu, Han; Zhang, Desheng; Xu, Tao; Gan, Yu (Frontiers in Ecology and Evolution, 2022)
The rubber expansion in Asian countries has led to various environmental problems. To smoothly promote the ecological restoration programs, an essential premise is that the local government must consider public attitude and understand the public willingness to pay (WTP) for restoration programs. This study adopts an integrated contingent valuation (CV) survey to empirically assess the non-market value and analyze the determinants of implementing rubber plantation ecological restoration(RPER) programs in Hainan, China. Given the consideration of the reasonable assumption of the respondents’ real WTP range, the Point and Interval Data (PID) model is constructed for estimation. Results show that the mean value of WTP for the RPER program is 178 yuan per year, and the total non-market value throughout the province is worth approximately 1.839 billion yuan per year after controlling the regional differences. In addition, individuals’ characteristics such as age, education level, family burden, income, and the residents’ environmental knowledge significantly impact the WTP for the restoration programs. Our findings add to the evidence that using the improved estimation methods can generate diverge results, and neglecting the bias caused by the usual interval data model would lead to downward biased estimates.